1989
DOI: 10.1101/gad.3.12a.1982
|View full text |Cite
|
Sign up to set email alerts
|

Histone H1 subtype-specific consensus elements mediate cell cycle-regulated transcription in vitro.

Abstract: In this study we used nuclear extracts from centrifugally elutriated cell populations to study histone HI transcriptional regulation during the cell cycle. Analysis of mutations within the HI promoter establish that both of the HI subtype-specific consensus elements participate in induction of transcription upon entry into S phase. The DNA binding activity of H1TF2, which specifically interacts with the HI proximal subtype-specific element, is increased in S-phase nuclear extracts, whereas no increase in DNA b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
0
1

Year Published

1991
1991
1999
1999

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(43 citation statements)
references
References 22 publications
1
41
0
1
Order By: Relevance
“…They showed a decrease in S-phase-dependent transcriptional induction compared with cells in G,, upon removal of either the H1 or CCAAT box. In contrast to Dalton and Wells [13] they did not observe an increase of the H1-box-binding factor HlTFl at S phase.…”
Section: Electrophoretic Mobility-shift Analysismentioning
confidence: 67%
See 2 more Smart Citations
“…They showed a decrease in S-phase-dependent transcriptional induction compared with cells in G,, upon removal of either the H1 or CCAAT box. In contrast to Dalton and Wells [13] they did not observe an increase of the H1-box-binding factor HlTFl at S phase.…”
Section: Electrophoretic Mobility-shift Analysismentioning
confidence: 67%
“…This conclusion was based on run-off transcription, H1-box mutation, gel mobility-shift assays and DNase protection studies [12]. Gallinari et al [13], however, concentrated on the cooperative action of factors binding to the H1 and CCAAT boxes. They showed a decrease in S-phase-dependent transcriptional induction compared with cells in G,, upon removal of either the H1 or CCAAT box.…”
Section: Electrophoretic Mobility-shift Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…However, the authors concluded that other sequences in the proximal promoter may contribute to the increased transcription of H1 genes during the S phase. Up to now, attempts to purify the trans-acting factor that putatively interacts with the H1 box (termed either H1-SF [26] or H1TF1 [45]) were without success.…”
Section: Discussionmentioning
confidence: 99%
“…Van Wijnen et al [1988a, bl and Gallinari et al [19891 have identified additional H1 specific transcription factors (termed HiNF-B or HlTF2, they may be identical), which both interact with the CCAAT-sequence. DNA binding studies indicate that the CCAAT box binding factor plays a major role in the S-phase regulation, since the HlTF2 activity is increased in S-phase nuclear extracts [La Bella et al, 1989;Heintz, 19911. As shown in Figure 1, the CCAAT box is missing in Hl0/H5-type gene promoters but is present in the upstream regions of H l t and main type H1 genes.…”
Section: H14mentioning
confidence: 99%